2019
DOI: 10.1007/s00216-019-01696-3
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted evaporative concentration combined with LC-HRMS/MS for ultra-trace-level screening of organic micropollutants in environmental water samples

Abstract: Vacuum-assisted evaporative concentration (VEC) was successfully applied and validated for the enrichment of 590 organic substances from river water and wastewater. Different volumes of water samples (6 mL wastewater influent, 15 mL wastewater effluent, and 60 mL river water) were evaporated to 0.3 mL and finally adjusted to 0.4 mL. 0.1 mL of the concentrate were injected into a polar reversed-phase C18 liquid chromatography column coupled with electrospray ionization to high-resolution tandem mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 22 publications
0
24
0
2
Order By: Relevance
“…To avoid the loss of very polar compounds during enrichment, the samples were concentrated via vacuum-assisted evaporative concentration using the Syncore® Analyst (BÜCHI, Switzerland) with slight modifications to the method validated by Mechelke et al (2019): 60 mL sample volume was filled into BÜCHI glass vials (0.3 mL appendix volume), spiked with 224 isotope labelled internal standards (ILIS) and evaporated at 20 mbar and 45 °C to 1-5 mL using the back-flush unit. The BÜCHI glass vials were rinsed with 1.5 mL H2O/methanol mix (85:15) to reduce analyte losses by sorption on the glass surface.…”
Section: Sample Enrichmentmentioning
confidence: 99%
“…To avoid the loss of very polar compounds during enrichment, the samples were concentrated via vacuum-assisted evaporative concentration using the Syncore® Analyst (BÜCHI, Switzerland) with slight modifications to the method validated by Mechelke et al (2019): 60 mL sample volume was filled into BÜCHI glass vials (0.3 mL appendix volume), spiked with 224 isotope labelled internal standards (ILIS) and evaporated at 20 mbar and 45 °C to 1-5 mL using the back-flush unit. The BÜCHI glass vials were rinsed with 1.5 mL H2O/methanol mix (85:15) to reduce analyte losses by sorption on the glass surface.…”
Section: Sample Enrichmentmentioning
confidence: 99%
“…4, pattern 2). Compounds following this pattern were reviewed for retention time plausibility using the linear relationship (r 2 =0.67) between predicted logDOW (at mobile phase pH 3) and STD retention times (n=590) from literature for the same liquid chromatographic system (predicted retention time = (predicted logDOW,pH3 + 5.4) × 0.42 -1 min) (Mechelke et al, 2019). In case of duplicates at different retention times, only the most intense compound was considered (resulting in n=802 TP suspects).…”
Section: Screening For Further Transformation Productsmentioning
confidence: 99%
“…Internal standard peak areas for hydrochlorothiazide were extremely low and inconsistent (average absolute yield of 2.0%), while evaporation enhanced baseline noise for methotrexate-D3 sufficiently such that no internal standard peak was visible. Mechelke et al 15 also reported a relatively low yield of 16.6% for hydrochlorothiazide in a surface water matrix.…”
Section: Quality Assurancementioning
confidence: 98%
“…The 20 mL samples were transferred to glass vials with 0.3 mL residual volume before they were spiked with 10 mL of an internal standard mixture (2.5 ng of each isotope-labeled standard in methanol). Concentration followed the method of Mechelke et al, 15 reducing samples to less than 0.5 mL under 20 mbar, 200 orbital revolutions per minute, and a slightly modi-ed temperature of 60 C over approximately 4 to 5 hours. The sides of the vials were washed down rst twice with 0.75 mL methanol, and then with 1 mL Milli-Q water when the evaporation neared completion.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation